The Effect of COVID-19 Diagnosis on the Physical, Social, and Psychological Well-Being of People in the United Arab Emirates: An Explorative Qualitative Study - AlKuwaiti, Mouza; Hamada, Bayan Abu; Aljneibi, Noof; Paulo, Marília Silva; Elbarazi, Iffat (Frontiers in Public Health, 2022)
A positive COVID-19 infection may impact physical, mental, and social health. Different factors may influence these impacts on different levels due to personal circumstances. This study aimed to explore the impact of a positive COVID-19 diagnosis on the physical,mental, social, psychological health, and lifestyle practices of an individual in the United Arab Emirates. A sample of 28 participants was interviewed using online interviews. An interview guide was created based on the coping strategy model and conceptual framework of coping strategies. All interviews were recorded; then transcribed after obtaining written consent from participants. The NVivo software was used for thematic analysis based on both identified coping models. Major themes included the physical effects, social effects, psychological effects, spiritual effects, and lifestyle effects. Emerging themes include coping mechanisms, trust in authorities and the health care system, appreciation of the role of the government, conspiracy theories, and media roles. This study indicates that people diagnosed with COVID-19 have perceived very good support in terms of their physical health from the government and health authorities, but require social, psychological, and educational support during the infection period and post-recovery.